Fuzzy Content-Based Retrieval in Image Databases - JIAN, Kang Wu (Institutional Knowledge at Singapore Management University, 1998)
Image data are inherently visual. The description of visual characteristics of images are imprecise. Fuzzy retrieval of images stored in a feature-based image database is a natural means to access the data. Unfortunately, to the authors knowledge, little work has been done on fuzzy image database models and fuzzy retrieval of feature-based image databases. In this paper, a fuzzy image database model and a concept of fuzzy space are proposed and fuzzy query processing in fuzzy space and fuzzy indexing on complex fuzzy vectors are described. An example image database, the computer-aided facial image inference and retrieval system (CAFIIR), is used for explanation throughout the paper.